An experimental model for assessing abrasion and erosion damage of coral concrete under flow conditions - PHAM, Duc-Phong; PHAM, Duc-Tiep (Edelweiss Applied Science and Technology, 2025)
Coral concrete is a structural solution for building breakwaters in coastal areas and offshore islands. However, in the marine environment, this structure is often affected by waves and currents carrying coral sand, causing the structure to gradually abrade and erode, affecting the quality of the project. This study builds a laboratory experimental model with five different ages of coral concrete (1, 3, 7, 14, 28 days) to assess the level of abrasion and erosion. The results show that coral concrete has the same compressive strength with repeated loading as regular concrete, but its resistance to abrasion and erosion is worse. 3D scanning results show that concrete samples under 7 days have relatively profound material loss. At 7 and 28 days, coral concrete lost 22.3% and 15.3% of mass due to abrasion and erosion, respectively, compared to regular concrete. Therefore, it is necessary to improve the abrasion and erosion resistance of coral concrete to ensure the durability and longevity of the structure when constructed on offshore islands.